Did the sunset of bureaucracy occur in Lithuania? The impact of recommendations provided by the sunset commissions on public management policy in 1999–2016 - Bortkevičiūtė, Rasa; Nakrošis, Vitalis (Politologija, 2018)
[full article and abstract in Lithuanian; abstract in English] Lithuania has a fragmented advisory system, with a total of 213 advisory bodies working at the central level of government in 2017. Ad hoc advisory bodies have low average lifespans, while the permanent advisory bodies usually have small administrative capacities. The Sunset Commissions were an exception because they advised Lithuanian governments for more than ten years – having been active since 1999 – and operated within a well-developed institutional framework. They provided recommendations on how to improve the efficiency and quality of public management for five Lithuanian governments until 2016 when Skvernelis’s government decided to discontinue its activities. There was almost no systematic monitoring of the extent to which the recommendations were carried out. Therefore, it is important to analyze the impact of the Sunset Commissions’ recommendations on public management policy in Lithuania. By combining the advisory systems and public policy process literature, the article identifies the main factors that may affect the successful use of advice: the compatibility of recommendations with the dominant political ideas, the composition of an advisory body, the government’s expectations toward its purpose, economic conditions, the support of the parliamentary majority and the political attention to its recommendations and the role of the changing leaders during public management reforms. Our empirical study – which was based on desk research, an analysis of administrative information, interviews and a survey of the Commissions’ members – consisted of two main stages. First, we assessed the impact of the Sunset Commissions on public management policy. Second, we determined the causal configurations underpinning the adoption and implementation of the recommendations set out by this advisory body. The results of our assessment reveals a good deal of variation in the use of the Commissions’ recommendations. The 1999–2000 and 2009 Commissions were the most successful in terms of the recommendations adopted and implemented. The lifespan of these Sunset Commissions was marked by economic downturns that opened “windows of opportunity” for major reforms. These advisory bodies are also characterized by high performance indicators. In contrast, the advisory bodies that worked during 2006–2008 and 2013–2016 received less political attention in the Lithuanian government in the context of economic growth, which made implementation more difficult. Overall, our assessment suggests that a more active performance of the advisory body is not sufficient to explain the level of adoption and implementation of its recommendations, as the political and economic conditions significantly shape the use of advice. The second part of the empirical study allowed us to determine the main causal configurations that explain the adoption and implementation of the recommendations suggested by the Sunset Commissions. The most important condition for successful adoption is the compatibility of advice: in other words, the more the given advice corresponds to a particular government’s priorities, the more successful the use of recommendation becomes. In addition, the uptake of recommendations is more frequent during economic downturns as well as when prime ministers exercise transformational leadership during the reform process. Meanwhile, the composition of the advisory body, the expectations of the government toward its performance and the leadership exercised by the heads of the commissions are less important. The conditions for the successful implementation of recommendations are slightly different. Although transformational leadership maintains its importance during the implementation phase, the exercise of transactional leadership can also lead to an incremental change if policy implementation is pursued adequately at the administrative level. To conclude, our research reveals that the Sunset Commissions had a substantial impact on Lithuanian public management policy. Even though the effectiveness of the advisory body varied during the rule of the Lithuanian governments, a majority of the Commissions’ members agreed that its work should be continued. The research also allows us to offer practical recommendations for the further performance of the Sunset Commissions. The main suggestions include, but are not limited to, strengthening the mandate of the Commission, enhancing administrative discipline during the execution of the recommendations and allocating financial resources for supporting the performance of the Commission.